S135 Can your mobile phone improve your asthma?. (16th November 2010) - Ryan, D; Pinnock, H; Tarassenko, L; Lee, A; Sheikh, A; Price, D
Abstract : Background: It is recognised that some 45% of the population exhibit poor asthma control. Over 90% of the population possess a mobile phone (>70% over 60 years of age). Mobile technology potentially addresses the barriers of low expectations and poor concordance which are factors in poor asthma control. Hypothesis: Using mobile phone recording of symptoms, lung function and medication use with instant feedback of asthma control, would improve control compared to using paper diaries. Trial design: A 6-month researcher-blinded randomised controlled trial Setting: UK primary care Method: Using central randomisation, we allocated patients ≥12 years of age with poorly controlled asthma (ACQ>1.5) to either mobile phone or paper-based monitoring. Clinical care was provided by practice asthma nurses in accordance with SIGN/BTS guidelines. Patients were reviewed monthly until control was achieved. A researcher, blinded to allocation assessed outcomes at 3 m and 6 m. Primary outcome measure: change in Asthma Control Questionnaire score between baseline and 6 months. Results: We randomised 288 patients from 32 practices (209 completed). Baseline characteristics of both groups were similar. Intention to treat analysis, before breaking the randomisation code, showed that control in both groups improved significantly and to a similar extent. ACQ: Group 1 (n=110) Baseline 2.17, 6m 1.25: Group 2 (n=99) Baseline 2.33, 6m 1.17. Mean (95% CI) improvement in ACQ: Group 1 (n=110) 0.84 (0.67, 1.02), Group 2 (n=99) 0.94 (0.77, 1.11) both p<0.001. Between group p=0.434 ns. Approximately 70% in each group improved by ≥0.5 (minimal clinically important difference). Abstract S135 Table 1 ACQ6 score Group 1(n=110) Group 2(n=99) Between group p value Baseline, median (IQR) 2.17 (1.67–2.67) 2.33 (1.67–2.67) 0.441 6 months, median (IQR) 1.25 (0.67–1.83) 1.17 (0.67–1.83) 0.995 Median difference (IQR) 0.83 (0.17–1.50) 0.83 (0.33–1.33) 0.586 Within group p value ( Wilcoxon ) <0.001 <0.001 Mean difference (95% CI) 0.84 (0.67 to 1.02) 0.94 (0.77 to 1.11) 0.434 Within group p value ( t-test ) <0.001 <0.001 MID *, n (%) 0.652  Improvement = MID 74 (67.3) 73 (73.7)  Improvement < MID 20 (18.2) 16 (16.2)  Deterioration < MID 6 (5.5) 5 (5.5)  Deterioration = MID 10 (9.1) 5 (5.1) Conclusion: Both groups demonstrated significant improvement in asthma control from baseline. Use of mobile phone technology provided no additional benefit over paper diaries.